2014
DOI: 10.3310/pgfar02010
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Stroke Calls: Obtaining Rapid Telephone Triage (ESCORTT) – a programme of research to facilitate recognition of stroke by emergency medical dispatchers

Abstract: BackgroundRapid access to emergency stroke care can reduce death and disability by enabling immediate provision of interventions such as thrombolysis, physiological monitoring and stabilisation. One of the ways that access to services can be facilitated is through emergency medical service (EMS) dispatchers. The sensitivity of EMS dispatchers for identifying stroke is < 50%. Studies have shown that activation of the EMSs is the single most important factor in the rapid triage and treatment of acute stroke p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…One key barrier may be the words and phrases used by 9–1-1 callers. A prior study of emergency calls for stroke, conducted in the ethnically and linguistically homogenous region of North West England, found that only 25% of callers conveyed a concern for stroke and even fewer described focal neurologic deficits 22,23,27. Our results confirm these prior findings for a diverse, urban population in the United States.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…One key barrier may be the words and phrases used by 9–1-1 callers. A prior study of emergency calls for stroke, conducted in the ethnically and linguistically homogenous region of North West England, found that only 25% of callers conveyed a concern for stroke and even fewer described focal neurologic deficits 22,23,27. Our results confirm these prior findings for a diverse, urban population in the United States.…”
Section: Discussionsupporting
confidence: 86%
“…Limiting EMD protocols to classical stroke descriptors, such as focal weakness, slurred speech, and facial droop, may not account for commonly used words and phrases used by lay callers and may hamper stroke recognition by EMDs 22,23. Our goal was to describe the words and phrases commonly used during 9–1-1 calls for acute stroke in a large United States city using both qualitative and quantitative methodologies.…”
Section: Introductionmentioning
confidence: 99%
“… 39 – 42 Recognition of stroke and TIA symptoms by members of the public is often poor, and coordination of Emergency Medical Services (EMS) and ED services, although improving, remains variable. 39 45 Mass media campaigns, including in the UK, the Face, Arms, Speech, Time (FAST) campaign, had some effect in increasing public awareness of stroke and TIA but have largely been proven ineffective in changing the behavior. 39 , 41 43 In the Barriers to the Early Assessment of TIA and Stroke (BEATS) study 41 and in qualitative studies, 42 , 46 reasons given for not seeking urgent medical attention included nonrecognition of symptoms, failure to appreciate the seriousness of symptoms, and uncertainty about the appropriateness of seeking urgent help, especially when symptoms were mild or transient.…”
Section: Recognition Of Stroke and Transient Ischemic Attackmentioning
confidence: 99%
“…Time to specialist assessment is critical in reducing mortality and improving outcomes after stroke and TIA. In the Emergency Stroke Calls: Obtaining Rapid Telephone Triage (ESCORTT) 40 , 45 study, researchers analyzed calls (n=592) to EMS to determine the relationship between callers’ description of potential stroke symptoms to EMS dispatchers and subsequent classification and prioritization of EMS responses. Jones et al 40 reported that callers who identified the patient was having a stroke were correct in 89% of cases.…”
Section: Recognition Of Stroke and Transient Ischemic Attackmentioning
confidence: 99%
See 1 more Smart Citation